Analysis of the teaching-learning methodology adopted in the introduction to computer science classes - Dias Canedo, Edna; Santos, Giovanni Almeida; Andrade de Freitas, Sergio Antonio (2017 IEEE Frontiers in Education Conference (FIE), 2017)
To meet socio-cultural demands imposed by the new millennium and its implications for education, it was necessary for teachers and students to participate actively in the teaching-learning process. In this context, the classes' evaluation by students has been a tool widely used in various universities in different countries. For institutions and teachers, these assessments allow knowing and measuring the results, further analysis of the institutional status, reviewing projects, adjusting goals, diagnosing weaknesses and correcting possible deviations. For the monitoring and improvement of this process, it was necessary to create instruments that aimed to evaluate the performance of the proposed changes. The teaching-learning methodology adopted in the Introduction to Computer Science classes may be a process that makes it difficult to understand the principles of language programming for undergraduate students in Computer Science and related areas, generating high failure and course drop out rates. This paper presents an analysis of the results obtained in the Introduction to Computer Science classes taught in five Engineering courses, of the Faculty of Gama (FGA) at University of Brasília (UnB). It was analyzed the evaluation questionnaire answered by the undergraduate students in 2017, perform validation of the questionnaire, check the level of students satisfaction in relation to the evaluated subject and the association among the level of satisfaction, the percentage of practical activities of the discipline, student performance and the level of absenteeism. 519 responses were studied, 63% of students reported satisfaction with the classes taken, however a significant number of students 37% reported dissatisfaction with assessment practices and the dynamics of the classes.